L-Menthol alleviates cigarette smoke extract induced lung injury in rats by inhibiting oxidative stress and inflammation via nuclear factor kappa B, p38 MAPK and Nrf2 signalling pathways. Issue 17 (5th March 2018) - Liu, Yan; Li, Ang; Feng, Xiuli; Jiang, Xiaoyan; Sun, Xiao; Huang, Weizhen; Zhu, Xiaosong; Zhao, Zhongxi
Abstract : l -Menthol is the main ingredient of peppermint which affects various pharmacological effects such as anti-inflammation and anti-oxidative activity. Abstract : l -Menthol is the main ingredient of peppermint which affects various pharmacological effects such as anti-inflammation and anti-oxidative activity. In this study, we aimed to evaluate the potential effects ofl -menthol on cigarette smoke extract (CSE) induced lung injury in rats. Morphology assessment results revealed that administration withl -menthol (5, 10 or 20 mg kg −1 d −1 ) significantly alleviated CSE-induced lung injury. Besides, l -menthol significantly reduced the inflammatory response by suppressing the production of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin-6 (IL-6) via downregulating nuclear factor kappa B (NF-κB) and p38 MAPK pathways. Meanwhile, l -menthol decreased the levels of oxidative stress markers including malondialdehyde (MDA) and myeloperoxidase (MPO) whereas it increased the amount of glutathione (GSH), glutathione peroxidase (GSH-Px), superoxide dismutase (SOD) and total antioxidant capacity (T-AOC) through activation of the Nrf2 pathway. Furthermore, the expression of MMP-9 and TIMP-1 in lungs was reduced after treatment withl -menthol, and this indicated thatl -menthol might have a potential effect on airway remodeling. Moreover, immunohistochemistry analyses indicated thatl -menthol could suppress the infiltration of CD4 + and CD8 + T cells in lung tissues and this was probably due to the immune regulation activity ofl -menthol. Taken together, our findings support thatl -menthol might be a potential candidate for the treatment of CSE-induced lung injury in rats.